The Top-Quark Mass: Challenges in Definition and Determination - Corcella, Gennaro (Frontiers in Physics, 2019)
The top-quark mass is a parameter of paramount importance in the Standard Model, playing a crucial role in the electroweak precision tests and in the stability of the Standard Model vacuum. I will discuss the main strategies to extract the top-quark mass at the LHC and the interpretation of the measurements in terms of well-posed top-mass definitions, taking particular care about renormalon ambiguities, Monte Carlo event generators and theoretical uncertainties.